W.A. Milliken and John J. Vertrees (Editors), Code of Tennessee, Being a Compilation of the Statute Laws of the State of Tennessee, of a General Nature, in Force June 1, 1884, 1060-61 (1884), § 5533 - (:unkn) unknown (My University, 1879)
Banned concealed carry of any dirk or razor. Also banned the carry of any sword-cane, loaded cane, slung-shot, brass knuckles, Spanish stilletos, belt pistols, pocket pistols, revolvers, any kind of pistol.
Keywords: CARRY; CARRY - CONCEALED - NON-GUN ARMS